IDENTIFICATION OF DROUGHT TOLERANCE OF SOME WEST SUMATERA LOCAL RICE (Oryza sativa L.) AT GERMINATION STAGE USING PEG 8000 - Sakinah Azhari; Violita Violita (Universitas Negeri Padang, 2019)
Drought-tolerant hybrid rice breeding certainly requires parental lines who are also tolerant to drought. The selection of superior rice elders usually comes from local rice. Polyetilene glycol (PEG) has been widely used as an osmotic solution to detect plant drought tolerance in the germination phase, especially PEG 6000. This study aims to determine the effect of PEG 8000 on rice germination and find out local drought tolerant rice varieties using drought susceptibility index (DSI) values through several germination variables, namely germination percentage, shoot length and seminal root, weight of shoots and seminal roots. The experiment was conducted at the Integrated Research Laboratory, Biology Department, FMIPA State University of Padang, using factorial randomized block design with 2 factors 3 replications with the first factor being 6 rice varieties while the second factor was 3 levels of PEG 8000 concentrations (PEG 8000 0%, 10% and 20%). If the DSI value is ≤ 0.5 then the variety is tolerant, if 0.5 <DSI ≤1.0 then the variety is medium and if DSI> 1.0 then the variety is intolerant (sensitive). The classified tolerant variety is Harum and Baroto; while sensitive varieties is Keriting and Batang Palo. The classified moderat variety is Situbagendit and Randam Kaus.